Escargot maintains stemness and suppresses differentiation in Drosophila intestinal stem cells - Korzelius, Jerome; Dutta, Devanjali; Gläßer, Christine (The EMBO journal, 2014)
Abstract Snail family transcription factors are expressed in various stem cell types, but their function in maintaining stem cell identity is unclear. In the adult Drosophila midgut, the Snail homolog Esg is expressed in intestinal stem cells (ISCs) and their transient undifferentiated daughters, termed enteroblasts (EB). We demonstrate here that loss of esg in these progenitor cells causes their rapid differentiation into enterocytes (EC) or entero-endocrine cells (EE). Conversely, forced expression of Esg in intestinal progenitor cells blocks differentiation, locking ISCs in a stem cell state. Cell type-specific transcriptome analysis combined with Dam-ID binding studies identified Esg as a major repressor of differentiation genes in stem and progenitor cells. One critical target of Esg was found to be the POU-domain transcription factor, Pdm1, which is normally expressed specifically in differentiated ECs. Ectopic expression of Pdm1 in progenitor cells was sufficient to drive their differentiation into ECs. Hence, Esg is a critical stem cell determinant that maintains stemness by repressing differentiation-promoting factors, such as Pdm1.
Gesehen am 23.10.2020